Maize and dietary change in early Peruvian civilization: Isotopic evidence from the Late Preceramic Period/Initial Period site of La Galgada, Peru - Washburn, E.; Nesbitt, J.; Burger, R.; Tomasto-Cagigao, E.; Oelze, V.M.; Fehren-Schmitz, L. (Elsevier, 2020)
The Late Preceramic Period (3000–1700 BCE) and Initial Period (1700–800 BCE) in Peru was a time of emergent social complexity as illustrated by the construction of ceremonial architecture and permanent settlements. A long-standing debate centers on the nature of the subsistence economies that supported this incipient complexity. Though some scholars consider maize to have been an agricultural staple at this time, a growing body of archaeological research indicates that the use of maize spread irregularly throughout Peru and did not become a dietary staple until sometime after c. 800 cal BCE. Using stable isotope analysis (δ¹³C and δ¹⁵N) of human bone and dentine, together with radiocarbon dating, this study estimates dietary composition, as well as changing subsistence strategies among 32 individuals interred within the ceremonial center of La Galgada (2300–1300 cal BCE). Our data suggests that maize was not a dietary staple in either the Late Preceramic or the Initial (1700–800 cal BCE) Period occupations at La Galgada. Instead the modeled diet (SIAR Mixing Model) suggests a continued reliance on locally available food sources (i.e. primarily C₃, legumes and grazing fauna). This finding combined with archaeological evidence indicates that diet remained relatively similar during the site’s occupation. Three radiocarbon dates generated for this study also indicate the re-use of La Galgada as a cemetery during the Late Intermediate Period (LIP) (1150–1450 cal CE). Diet during the LIP exhibits a significant change, with a decrease in the proportion of C₃ and legumes and an increase in the proportion of meat. This study highlights the utility of mixing models to reconstruct past human diet, allowing for a more comprehensive understanding of potential differences in the proportions of food types over time.
Keywords: Stable isotope ratios; Maize; Peru; Late Preceramic Period; Initial Period; Late Intermediate Period; Dietary mixing models; https://purl.org/pe-repo/ocde/ford#5.04.03